Adherence of NSAID Administration in Patients with Mild and Moderate Traumatic Brain Injury in Dr. Soetomo General Hospital, Surabaya - Finna Permata Putri; Agus Turchan; Nurmawati Fatimah; Muhtarum Yusuf (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2021)
Introduction: Traumatic brain injury (TBI) has a concerning incidence rate. One of the therapies for patients with TBI is non-steroidal anti-inflammatory drugs (NSAID) administration as an analgesic with proper adherence to achieve optimal therapy results. This research aimed to evaluate physicians’ NSAID administration adherence in patients with mild and moderate TBI in Dr. Soetomo General Hospital, Surabaya.Methods: This was an observational descriptive study with a retrospective design. NSAID administration adherence was graded by evaluating the dose, route, frequency, and interval of NSAID administration. The variables were evaluated by observing the medical records of inpatients with mild and moderate TBI from 1 January to 31 December 2018.Results: NSAIDs used for TBI management were metamizole, paracetamol, mefenamic acid, and ketorolac. Metamizole was administered in 10 patients (34.5%), paracetamol in 1 patient (3.4%), metamizole and  paracetamol in 15 patients (51.7%), metamizole and mefenamic acid in 1 patient (3.4%), metamizole and paracetamol with mefenamic acid in 1 patient (3.4%), and metamizole and ketorolac in 1 patient (3.4%). Adherence of paracetamol, mefenamic acid, and ketorolac administration in patients with mild and moderate TBI were well-administered in every evaluated variable. Metamizole administration’s adherence was already well-administered in drug dosage and drug administration route, but it was not well-administered in drug administration interval and frequency.Conclusion: Physicians’ adherence to NSAID administration in patients with mild and moderate TBI in Dr. Soetomo General Hospital, Surabaya was well-administered, except for metamizole.